Economic and environmental efficiency of joint R&D between universities and firms - Fang, Zhong; Lv, Siqi; Chiu, Yung-ho; Lin, Tai-Yu; Lin, Yi-Nuo (Technological and Economic Development of Economy, 2023)
China’s total R&D funding has increased from CNY 89.6 billion in 2000 to CNY 2,442.6 billion in 2020 or by 27 times in 20 years. Although a large amount of literature has analyzed China’s R&D efficiency, scant studies have targeted second-stage economic and environmental efficiencies and rarely considered both university and industrial R&D. This research thus uses the Parallel Two-stage Undesirable Dynamic Model to evaluate the R&D efficiencies of universities and industry and examines their impact on the economy and the environment. The empirical results are as follows. 1) There are differences in the R&D and environmental efficiency of various regions in China with the eastern part being the highest, the western part second, and the central part the lowest. 2) The input index efficiency of universities is generally higher than that of industry. 3) The linkage effect between universities and the local economy and the environment is higher than that of industry. First published online 13 February 2023